Preparation of an enterprise for emergency situations and their better communication - Bienias, Małgorzata; Czerniak, Kinga; Ewertowski, Tomasz (Przygotowanie przedsiębiorstwa produkcyjnego na sytuacje awaryjne i lepsza komunikacja dotycząca sytuacji awaryjnych w przedsiębiorstwie, 2019)
The article presents issues related to emergency situations, referring to legal and normative requirements (in particular ISO 45001 and ISO 14001). After defining what an emergency situation is and indicating the differences between it and a crisis situation, arguments in favour of preparing companies for such situations were presented. In order to identify those threats that may cause an emergency situation, the threats were identified and risk assessed using a matrix method used by the Government Security Centre, modified for the purposes of research. This was followed by detailed guidelines for the drafting of the procedures to ensure its completeness, and a general scheme for it was proposed. Finally, technological proposals to improve communication and facilitate access to emergency procedures were presented and conclusions drawn
Informatyka Ekonomiczna = Business Informatics, 2019, Nr 3 (53), s. 9-22
Keywords: emergency situation; accidents; safety; risk assessment; communication; sytuacja awaryjna; awarie; bezpieczeństwo; ocena ryzyka; komunikacja